2005
DOI: 10.1162/089892905774597272
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Vestibular Rotatory Accelerations on Covert Attentional Orienting in Vision and Touch

Abstract: Abstract& Peripheral vestibular organs feed the central nervous system with inputs favoring the correct perception of space during head and body motion. Applying temporal order judgments (TOJs) to pairs of simultaneous or asynchronous stimuli presented in the left and right egocentric space, we evaluated the influence of leftward and rightward vestibular rotatory accelerations given around the vertical head-body axis on covert attentional orienting. In a first experiment, we presented visual stimuli in the lef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
40
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 60 publications
(63 reference statements)
5
40
0
Order By: Relevance
“…The sources of this vestibular alpha suppression are in line with the temporoparietal vestibular cortex previously identified (Bense et al 2001;Dieterich et al 2003;Hewett et al 2011;Kahane et al 2003;Lobel et al 1998;Lopez and Blanke 2011). Future work should distinguish how the present vestibular alpha oscillations compare to alpha oscillations over parietal regions previously linked to attentional (Haegens et al 2011(Haegens et al , 2012Romei et al 2008;Sauseng et al 2005) and related (i.e., FerrĂš et al 2014;Figliozzi et al 2005) processes. Unlike studies of visual and somatosensory attention that showed a lateralization of alpha suppression (Haegens et al 2011(Haegens et al , 2012, we note that there was no significant difference between alpha suppression when comparing the early periods of CW and CCW rotation in study 2 and no lateralized topographies across all studies (Fig.…”
Section: Vestibular Alphasupporting
confidence: 80%
“…The sources of this vestibular alpha suppression are in line with the temporoparietal vestibular cortex previously identified (Bense et al 2001;Dieterich et al 2003;Hewett et al 2011;Kahane et al 2003;Lobel et al 1998;Lopez and Blanke 2011). Future work should distinguish how the present vestibular alpha oscillations compare to alpha oscillations over parietal regions previously linked to attentional (Haegens et al 2011(Haegens et al , 2012Romei et al 2008;Sauseng et al 2005) and related (i.e., FerrĂš et al 2014;Figliozzi et al 2005) processes. Unlike studies of visual and somatosensory attention that showed a lateralization of alpha suppression (Haegens et al 2011(Haegens et al , 2012, we note that there was no significant difference between alpha suppression when comparing the early periods of CW and CCW rotation in study 2 and no lateralized topographies across all studies (Fig.…”
Section: Vestibular Alphasupporting
confidence: 80%
“…Previous studies have suggested that spatial attention is strongly coupled to vestibular mechanisms, such that passive own-body displacements result in an automatic shift of attention in the rotation direction of one's body (Figliozzi, Guariglia, Silvetti, Siegler, & Doricchi, 2005;Karnath & Dieterich, 2006). The MBT task used in the present study had a strong spatial component (i.e., colored hand of the avatar appearing at the left or the right side of the screen).…”
Section: Discussionmentioning
confidence: 86%
“…Whereas these previous studies tested visual and vestibular integration with respect to self-motion and vestibular influences on the processing of consciously perceived visual information, other studies investigated the effects of vestibular stimulation on visual attention (Figliozzi, Guariglia, Silvetti, Siegler, & Doricchi, 2005), bistable visual states (van Elk & Blanke, 2012), and mental rotation (Grabherr et al, 2011;van Elk & Blanke, 2014). Of relevance for vestibular input to visual awareness, it was shown by van Elk & Blanke that the direction of passive self-motion influences the perceived rotation direction of bistable rotating stimuli (that under stationary conditions have 50% of chance to be perceived to be rotating in either direction).…”
Section: Incongruent Faster Incongruent Fastermentioning
confidence: 99%